Delineating Alzheimer's disease progression with MGAT3, a biomarker for improved prognosis and personalized therapy - Fiala, Milan; Porter, Verna (Biomarkers in medicine, 2011)
According to this immune hypothesis, two functional biomarker tests have been developed by: *Exposing freshly isolated PBMCs of AD patients to FAM-AÎ²(1 Âµg/ml overnight) and testing the AÎ²uptake by flow cytometry; *Challenging PBMCs with AÎ²(2 Âµg/ml overnight) and testing the transcription of MGAT3 (GnT-III) by reverse transcription PCR [5]. The flow cytometric test had a high sensitivity for AD (94%) and less sensitivity for mild cognitive impairment (60%), and a high specificity (100%) in highly cognitively active subjects age-matched to AD patients, but extremely low specificity (25%) in older caregivers. [...] a normal result of this test suggests the absence of AD, whereas an abnormal result may indicate AD or retirement- and age-appropriate cognitive function with unknown prognosis for future dementia.